My favorite pets by Gus W. for Ms. Smolinski's class - Birdsall, Jeanne (Alfred A. Knopf, 2016)
In his homework assignment, Gus spends less time on what he likes about sheep and more on how he has gotten in trouble doing such things as using a sheep as an umbrella, or letting sheep into his house.